2022
DOI: 10.1155/2022/8446281
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of an Assessment System for Business English Linguistics Based on RNN Multidimensional Models

Abstract: The current teaching evaluation system of the course “Introduction to Business English Linguistics” has many problems and should be reformed according to the requirements of the relevant professional syllabus. This paper proposes a recurrent neural network (RNN) modelling technique, which has achieved good results in modelling business English language models. The RNN modelling method is applied to Chinese language modelling according to the characteristics of Chinese language, and the advantages of the two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…If the input gate remains closed over time, the newly input data of the network will not be able to replace the previous incentive output of the unit. At any time, as long as the network output gate is opened, the valid data information can be referred to at any time, so that the network realizes the time distance step and obtains a more effective graphic relationship reference [13][14].…”
Section: Image-text Relationship Analysis Modelmentioning
confidence: 99%
“…If the input gate remains closed over time, the newly input data of the network will not be able to replace the previous incentive output of the unit. At any time, as long as the network output gate is opened, the valid data information can be referred to at any time, so that the network realizes the time distance step and obtains a more effective graphic relationship reference [13][14].…”
Section: Image-text Relationship Analysis Modelmentioning
confidence: 99%
“…Shi, Y proposed a recursive neural network modeling technique to address the problems of teaching evaluation in business English language courses, which achieved good results in business English language model modeling and also made up for the shortcomings of traditional teaching evaluation [6]. Lee, T. S. O et al mainly investigated the role of the teacher in the use of motivational strategies towards second language motivation in business English teaching and found that the teacher's perspectives have rarely been studied in detail.…”
Section: Related Workmentioning
confidence: 99%
“…In the process of cross-cultural communication, only students have good cultural awareness of foreign trade, based on different values and different cultural orientations, so that the communication becomes smoother and reduces conflicts and misunderstandings. Then, the development of business activities can be promoted smoothly [3][4][5]. Therefore, only by ensuring the practical cultivation of students' cultural awareness and the comprehensive development of students' abilities in business English teaching can the impact of cultural conflicts be avoided in the process of cross-cultural exchanges and ensure the smooth implementation of international business activities [6][7][8].…”
Section: Introductionmentioning
confidence: 99%